(untitled) (Archaeologia Adriatica, 2021)
The article deals with underwater archaeological finds discovered in front of a complex of outhouses in Muline in the north-western part of the island of Ugljan. The finds include mostly pottery fragments and some glass collected during brief archaeological trial trenching conducted in 1997. The majority of fragments are amphora shards, but fragments of fine sigillata as well as coarse kitchenware were also found, along with several tegulae fragments, two oil lamp fragments and a whorl. Unfortunately, a large number of finds cannot be typologically classified, as they represent amphora belly and body fragments that do not provide sufficient data for more detailed classification. The paper presents only part of the specimens which it was possible to classify with certainty. Their classification determines the time frame to which the entire Antiquity and Late Antiquity complex belongs.